CEO Narcissism, Audience Engagement, and Organizational Adoption of Technological Discontinuities. (June 2013) - Gerstner, Wolf-Christian; König, Andreas; Enders, Albrecht; Hambrick, Donald C.
We examine the responses of major pharmaceutical firms to the advent of biotechnology over the period 1980 to 2008 to explain why established firms vary in their adoption of technological discontinuities. Combining insights from upper echelons theory, personality theory, and research on organizational responses to new technologies, we posit that narcissistic chief executive officers (CEOs) of established firms will be relatively aggressive in their adoption of technological discontinuities. We propose, however, that the effect of a CEO's narcissism on organizational outcomes will be moderated by audience engagement—the degree to which observers view a phenomenon as noteworthy and provocative—which varies over time. When audience engagement is high, narcissistic CEOs will anticipate widespread admiration for their bold actions and thus will invest especially aggressively in a discontinuous technology. Drawing from work on managerial cognition, we further hypothesize that CEOs' narcissism will influence their top managers' attention to a discontinuous technology, an association that will also be moderated by audience engagement. Finally, we suggest that managerial attention to the discontinuous technology will subsequently be reflected in company investments in the new technological domain. Results provide considerable support for our hypotheses and highlight the role of narcissism in the context of radical organizational change, the influence of audience engagement on executive behavior, and the effect of executive personality on managerial attention.